Study on Cutting Form and Surface Machining Quality of Wheel Tread under Reprofiling - Jianxi Wang; Xin Xue; Yongjie Lu (Advances in Materials Science and Engineering)
The wheelset maintenance cost is an important part of train maintenance cost. Researchers and railway operators have been closely concerned about the way to minimize residual stress at wheel tread and surface roughness during wheel reprofiling, thereby reducing the wheel damage during operation, extending the wheelset service life, and cutting down wheelset maintenance cost. The present study involves dynamic simulation of tread reprofiling process by building a finite element model of wheel reprofiling, taking the wheel steel as research object. This paper makes a comprehensive analysis of surface roughness and residual stress distribution of wheel tread under different milling parameters. The simulation results indicate that the increase in cutting speed and back cutting depth causes the chip morphology to change while impairing the machined surface quality. Once serrated chip occurs, it means wheel tread machining quality deteriorates remarkably. In this way, the paper associates macroscopic chip morphology with microcosmic surface roughness and internal residual stress to provide theoretical basis for optimization of wheel reprofiling process.